International human resource management in an era of political nationalism. (28th November 2017) - Horak, Sven; Farndale, Elaine; Brannen, Mary Yoko; Collings, David G.
Abstract : In times of the "Brexit" and "America First" policies, several industrialized countries' governments are turning toward more national‐oriented migration policies. Simultaneously, societal aversion to immigration is growing. Both trends are sending negative signals to highly skilled employees and making immigrants feel that they are no longer welcome. Consequently, international careers are becoming uncertain, risky, and unpredictable. This new reality in industrialized knowledge‐based economies may affect firms' talent pool and the skill set available to a country. To shed light on the new environment of international human resource management, we interviewed Mary Yoko Brannen and David Collings, leading experts in the field, to explore their perspective on how the field is changing. The interviews reported here uncover fascinating insights, including the need to counteract the globalization fears in the West of the predominantly White working and lower‐middle class through education. Companies may also rethink their organizational boundaries and the notion of traditional employees by using their agility to counteract the political forces harming their talent pool strategy.